2002
DOI: 10.1002/path.1128
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic differences between histological subtypes of malignant mesotheliomas: DNA cytometry and comparative genomic hybridization of 90 cases

Abstract: It is established that subtypes of human malignant mesotheliomas (MM) are associated with different survival times. Ninety cases of MM were examined using DNA cytometry and comparative genomic hybridization (CGH), with emphasis on the main histological subtypes; epithelioid, sarcomatoid and biphasic. A comparison by DNA cytometry revealed moderate differences, with the rare subgroup of mesodermomas having the highest and the sarcomatoid group the lowest rate of aneuploidy. Using CGH, 6.2 chromosomal imbalances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 22 publications
9
49
1
2
Order By: Relevance
“…1A) as previously reported (7)(8)(9)35). The homozygous deletions of 9p21 were detected in all MM samples, and the allele losses of 22q were frequently found in all histological types of cells.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…1A) as previously reported (7)(8)(9)35). The homozygous deletions of 9p21 were detected in all MM samples, and the allele losses of 22q were frequently found in all histological types of cells.…”
Section: Discussionsupporting
confidence: 80%
“…Five purchased MM cell lines were also analyzed to compare with our primary cell cultures. Many molecular cytogenetic studies using karyotyping, CGH and array-based CGH have been performed and they show that the 1p, 3p21, 9p21 and 22q regions are frequently lost in MM (7)(8)(9). Chromosome 9p21 and 22q carry the tumor suppressor genes CDKN2A (cyclindependent kinase inhibitor 2A) and NF2 (neurofibromin 2), respectively, and there are many functional analyses of these genes (10)(11)(12)(13).…”
Section: Frequent Deletion Of 3p211 Region Carrying Semaphorin 3g Anmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative genomic hybridization (CGH) technique has recently been introduced to search for additional genes that are potentially involved in MM biology. New alteration regions have been identified, including 1q, 4q, 5p, 6p, 7p, 8p, 8q, 10p13-pter, 13q, 14q, 15q, 17p12-pter, 17q, and 20, in which new cancer-associated genes of MM may be harbored [27,28]. A recent study of array-based CGH analysis with MMs from a total of 22 individuals identified high-copy gain at 1p32, which includes the JUN protooncogene [12].…”
Section: Searching For New Key Genes In Malignant Mesotheliomamentioning
confidence: 99%
“…Many studies have been conducted to determine the key underlying genetic and epigenetic events responsible for the development of MM. Karyotyping, allele typing and comparative genomic hybridization analysis have demonstrated that most cases of MM have multiple chromosomal alterations, which include chromosome 9p21 and 22q (7)(8)(9)(10)(11)(12)(13)(14). Inactivation of the p16 INK4a /p14 ARF locus at the 9p21 locus is found in over 70% of MM samples (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%